Plasmodium falciparum variability and immune evasion proceed from antigenicity of consensus sequences from DBL6ε; generalization to all DBL from VAR2CSA. - Philippe Deloron (Public Library of Science (PLoS), 2013)
We studied all consensus sequences within the four least 'variable blocks' (VB) present in the DBL6ε domain of VAR2CSA, the protein involved in the adhesion of infected red blood cells by Plasmodium falciparum that causes the Pregnancy-Associated Malaria (PAM). Characterising consensus sequences with respect to recognition of antibodies and percentage of responders among pregnant women living in areas where P. falciparum is endemic allows the identification of the most antigenic sequences within each VB. When combining these consensus sequences among four serotypes from VB1 or VB5, the most often recognized ones are expected to induce pan-reactive antibodies recognizing VAR2CSA from all plasmodial strains. These sequences are of main interest in the design of an immunogenic molecule. Using a similar approach than for DBL6ε, we studied the five other DBL and the CIDRpam from VAR2CSA, and again identified VB segments with highly conserved consensus sequences. In addition, we identified consensus sequences in other var genes expressed by non-PAM parasites. This finding paves the way for vaccine design against other pathologies caused by P. falciparum.